If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-4)-3x=-4(x+2)+3x
We simplify the equation to the form, which is simple to understand
2(x-4)-3x=-4(x+2)+3x
Reorder the terms in parentheses
+(+2x-8)-3x=-4*(x+2)+3x
Remove unnecessary parentheses
+2x-8-3x=-4+*(+x+2+)+3x
Reorder the terms in parentheses
+2x-8-3x=+(-4x-8)+3x
Remove unnecessary parentheses
+2x-8-3x=-4x-8+3x
We move all terms containing x to the left and all other terms to the right.
+2x-3x+4x-3x=-8+8
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| x^4+10x^2-299=0 | | 4y-8-2y=2-(-2) | | -(8(0)+4)=4(0)-2(6(0)+2) | | 4x^2-20xy-7x+35y= | | 3x^2+23x-8= | | 3(x+2)-2=6(x+1)-3x | | 4y-8-27=2-(-2) | | 14x-79=8x-25 | | 4x-(x+3)=6 | | -10+5y-35=-4 | | -10+5-35=-4 | | 7a-b=15 | | 175=85+(15+8)w | | (x-78)+x=180 | | 3b-12=6b-8 | | m+1=-1+3m | | -4y+36=4(3y-3) | | 5x-1x=15 | | 3.4x+5=22 | | 2.5x+2.5=12.5 | | 2.1(a+0.5)=-2.1(a+20) | | -5t-7t=2t | | -5x-24=2x+11 | | 5(c-1)-2(c+3)-2c=-8 | | 23=-3m+2 | | 11-4z=-27 | | 4y-14=6y-16 | | -5t-7t= | | -8x+4=3x+4 | | (x+16)+(7x-20)=180 | | .5x+4=.66x+.5 | | -3a+16=-20 |